Electrochemically Tunable Proton‐Coupled Electron Transfer in Pd‐Catalyzed Benzaldehyde Hydrogenation. (12th December 2019) - Koh, Katherine; Sanyal, Udishnu; Lee, Mal‐Soon; Cheng, Guanhua; Song, Miao; Glezakou, Vassiliki‐Alexandra; Liu, Yue; Li, Dongsheng; Rousseau, Roger; Gutiérrez, Oliver Y.; Karkamkar, Abhijeet; Derewinski, Miroslaw; et al.
Abstract: Acid functionalization of a carbon support allows to enhance the electrocatalytic activity of Pd to hydrogenate benzaldehyde to benzyl alcohol proportional to the concentration of Brønsted‐acid sites. In contrast, the hydrogenation rate is not affected when H2 is used as a reduction equivalent. The different responses to the catalyst properties are shown to be caused by differences in the hydrogenation mechanism between the electrochemical and the H2 ‐induced hydrogenation pathways. The enhancement of electrocatalytic reduction is realized by the participation of support‐generated hydronium ions in the proximity of the metal particles. Abstract : Mit vereinten Kräften : Eine Reihe von Pd/C‐Katalysatoren mit modifizierten Kohlenstoff‐Trägermaterialien wurde für die elektrochemische Hydrierung von Benzaldehyd eingesetzt. Die Anwesenheit von Säuregruppen an der Metall/Träger‐Grenzfläche erhöht die katalytische Aktivität von Pd aufgrund der Mitwirkung von Brønsted‐sauren Zentren im Hydrierungsmechanismus.